Rethinking America's Highways : A 21st-Century Vision for Better Infrastructure - Poole, Robert W. (Chicago : University of Chicago Press, 2018)
Americans spend hours every day sitting in traffic. And the roads they idle on are often rough and potholed, their exits, tunnels, guardrails, and bridges in terrible disrepair. According to transportation expert Robert Poole, this congestion and deterioration are outcomes of the way America provides its highways. Our twentieth-century model overly politicizes highway investment decisions, short-changing maintenance and often investing in projects whose costs exceed their benefits. In Rethinking America's Highways, Poole examines how our current model of state-owned highways came about and why it is failing to satisfy its customers. He argues for a new model that treats highways themselves as public utilities-like electricity, telephones, and water supply. If highways were provided commercially, Poole argues, people would pay for highways based on how much they used, and the companies would issue revenue bonds to invest in facilities people were willing to pay for. Arguing for highway investments to be motivated by economic rather than political factors, this book makes a carefully-reasoned and well-documented case for a new approach to highways that is sure to inform future decisions and policies for U.S. infrastructure.
Frontmatter -- Contents -- Tables and Figures -- Preface -- Chapter 1. Our Troubled Highway System -- Chapter 2. How the Private Sector Is Reinventing America's Freeways -- Chapter 3. Where America's 20th-Century Highway Model Came From -- Chapter 4. The Rediscovery of Toll Road Companies Overseas -- Chapter 5. Toll Concessions Return to America -- Chapter 6. The Benefits of Long-Term P3 Concessions -- Chapter 7. Critics and Controversy: Opposition to Tolling and Long-Term Concessions -- Chapter 8. Highways as Network Utilities -- Chapter 9. Transforming the Interstate Highways -- Chapter 10. Transforming Urban Freeways -- Chapter 11. Challenges to the New Vision for US Highways -- Chapter 12. A New Future for US Highways -- Acknowledgments -- Notes -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 22. Okt 2019)
Keywords: Roads -- United States -- Finance; Transportation and state -- United States; BUSINESS & ECONOMICS / General